Literature Study: The Effect of Cold Water Immersion and Sport Massage Techniques on Muscle Pain - Afandi, Nur Rizal; Kushartanti, BM Wara; Hafidz, Abdul; Chen, Hocheng (Journal of Sport Science and Education, 2023)
Pain is the most common symptom of sports injuries. Studies suggest that sports massage and or cold-water immersion may improve pain. This study aimed to synthesize findings from previous research on sports massage and cold water immersion for pain treatment in athletes. Relevant article search method using the Garuda database, Onesearch, and Google Scholar originating from sinta 2 - 3 indexed journals with the keywords "Cold Water Immersion" + "Sports Massage Technique" + Pain." Article searches started from 2017 to 2022; literature analysis used PRISMA guidelines, and feasibility assessments used JBI critical assessment. Five articles were included in the literature review. Cold water immersion and sports massage techniques significantly affect the treatment of muscle pain. These two alternative interventions have been proven to alleviate the effects of muscle pain and speed up the healing process for athletes who experience muscle pain problems.